Cyclospora cayetanensis: An Infestation among Diarrheal Children in Kathmandu Valley, Nepal - Bhattachan, Balkrishna; Rai, Ganesh; Munankarmi, Nabin Narayan; Sherchand, Jeevan Bahadur (Nepal Journal of Biotechnology, 2019)
Cyclospora cayetanensis, a coccidian parasites which is responsible for recurring diarrhea and gastroenteritis especially among children living under poor hygienic condition in developing country like Nepal. Aimed of this research is to find out the prevalence of intestinal parasites and C. cayetanensis among diarrheal children in a Pediatric Hospital in Kathmandu valley, Nepal. Cross-sectional type of study was done. Altogether 196 stool specimens were collected from June to September 2013 among outpatient diarrheal children in Kanti Children’s Hospital. Modified Ziehl Neelson staining method was applied for detection of oocysts of Cyclospora after formal-ether sedimentation. Parasites were detected in 13.7% (27/196) of stool samples from ≤ 15 year old diarrheal patients. C. cayetanensis was detected in 4.8% (8/196). In genderwise, infection rate of C. cayetanensis 4.5 % (5/112), in male were higher than 3.6% (3/84) in female. In agewise, infection rate of C. cayetanensis in 5.7 % (3/52) 11-15 year old were highest followed by 4.1% (3/78) in 0-5 year old and 3.0% (2/66) in 6-10 year old. In seasonwise, infection rate of Cyclospora was highest in the month of August 7.4% (4/54) followed by 3.9% (2/51) in July, 2.3% (1/44) September and 2.1% (1/47) in June. Altogether five different type of parasites were detected. Infection rate of Giardia lamblia were highest 5.1 % (10/196) whereas lowest was Cryptosporidium parvum 1.0 % (2/196). Prevalence of C. cayetanensis is highly probable to infant, neonate, toddler and diarrheal children. Therefore, attention should be made in laboratory investigation of C. cayetanensis while suspecting the diarrheal patients infected with other parasites.